BARTHEL INDEX AND ITS ASSOCIATED HEALTH AND LIFE YEARS INDICATORS. (11th November 2018) - Feng, G; Lu, B; Mi, H
Abstract: Barthel index is widely used in determining long-term care (LTC) eligibility as part of the assessment criteria. We define partial dependent with Barthel index score of 0–15, and severe and total dependent with 20–35 and 40–55 (out of 100). Using a local administration dataset in China (N=23, 468), we estimate the Kapan-Meier probabilities in each state. We calculate remaining life expectancy (RLE) by age, gender and dependent status. Certain proportion of the dependent people are recovered and exit the system. Exit ratios are calculated so that the system turnover rates can be derived. We use Cox model for survival analysis and use probabilistic method for life expectancy and exit (recovery) ratio calculation. Our results show that female with total dependent status (Barthel 0–15) have a remaining life expectancy of 5.0 year and 3.4 year at age 60 and 80 respectively, while male have only 3.5 and 2.5 years. The difference narrows with less disability status. Recovery rate varies from 10–16% and has an average of 13.6%. Turnover rate in LTC institution is about 30%. This provide another way of estimating life expectancy, other than age. It also provides an prox. estimation for institutional care cost. The significant difference between female and male RLE in severe and total dependent status imply further research topics. The level of disability status and its associated RLE provide cost estimation and eligibility options for middle and low-income countries where resources are limited to provide any public funded LTC.